Incidencias de un sistema de acciones metodológicas en el desarrollo de la resistencia anaeróbica de futbolista de la categoría 12, 14 años club especializado y formativo San Antonio de la Parroquia Antonio Sotomayor - Díaz Rendón, Jimmy Wagner (2022)
The present degree work corresponds to the methodological action system theme for the development of anaerobic resistance, where the study was carried out in a professional and training club "San Antonio", which has the Antonio Sotomayor Parish that belongs to the Vinces Canton, which consists of 60 students in training, for which the objective set for this work is to analyze the level of incidence that a system of methodological actions has on young soccer players, including their ages from 12 to 14 years, through the involvement of anaerobic exercises that strengthen the aspect physical, to reach this end, an investigation was proposed under a descriptive approach, which combines qualitative and quantitative aspects, this allows the use of information collection techniques both in figures and descriptions, for which field research was also applied. to directly observe all the proposed exercises, once it is known that they are abajara with 22 students, which is the sample that was chosen, we proceeded to pass them the link of the digital questionnaire elaborated in Question Pro for analytical purposes that, through the results obtained, conclude that 65% of the respondents maintain that it is a fact that a lot of aerobic exercise decreases the quality of the muscles, so they feel the need to improve this factor a little, which is necessary to potentiate strength through an adequate application of anaerobic exercises, for which it is recommended that it is necessary to determine the appropriate use of aerobic exercises that decrease in muscular reduction, so that there is no imbalance, a proposal to solve this is an anaerobic-aerobic combination in the exercises that children receive, so that in this way the integral development of the minor is worked in a balanced way through a specific methodology.